Statistics of the seismicity of 2021 in Costa Rica - Linkimer, Lepolt (2021)
The National Seismological Network (RSN) located 3745 local earthquakes during 2021, which is equivalent to the seismic energy released by an event of magnitude (Mw) 6.9. The seismicity was mainly located in seven zones with 50-350 earthquakes. There were 209 felt events (~6% of the totality), including 31 with Mw between 5.0 and 6.7. Most of these earthquakes were shallow (~88% < 30 km), had a low magnitude (~52% Mw < 3.9), and were originated in faults within the Caribbean and Panama plates (~69%). The largest earthquake of the year of Mw 6.7 originated in the Panama Fracture Zone, without causing damage or casualties. Because all the earthquakes with Mw ≥ 5.5 were centered offshore and far from the population high intensities were not reported.